Determination of Helicobacter pylori Virulence Genes in Gastric Biopsies by PCR. (15th April 2013) - Essawi, Tamer; Hammoudeh, Wail; Sabri, Israr; Sweidan, Walid; Farraj, Mohammad A.
Abstract : Aim . The aim of this study was to identify the presence of H. pylori in biopsy specimens from symptomatic patients by PCR. In addition, the rate of cagA, vacA, iceA1, and iceA2 virulence genes was determined. Materials and Methods . One hundred antral gastric biopsy specimens were collected during endoscopy from patients suffering from gastroduodenal symptoms. The samples were collected by the gastroenterologists in their own clinics in Ramallah, Palestine. DNA was extracted from the biopsies and subsequently used for PCR identification of H. pylori and the virulence genes using specific primers. Results . The rate of positive H. pylori in the collected biopsies was 44%. The rates of the virulence genes in this sample: cagA, vacA, iceA1, and iceA2 were 65.9%, 40.9%, 63.6%, and 84.1%, respectively. Conclusion . The iceA2 gene was the most frequent in this study. Much research is necessary to determine the presence of an association of this gene with gastric pathology. Variation in the rates of the iceA gene in different countries is a strong indication of its geographical distribution. This study would provide important information regarding the prevalence of virulence genes ( vacA, cagA, iceA1, and iceA2 ) in H. pylori strains in the sample tested in this country.